ANALISIS ALGORITMA BACKPROPAGATION DALAM PREDIKSI NILAI EKSPOR (JUTA USD) - Jonas Rayandi Saragih; Mhd. Billy Sandi Saragih; Anjar Wanto (Jurnal Pendidikan Teknologi dan Kejuruan, 2018)
In a study, the analysis is necessary for the accuracy and accuracy of an education. So also in prediction Export Value (Million USD). This research will discuss the value of export in general in North Sumatra based on Million USD. This research is conducted to know the export development in North Sumatera in the future. This research uses Artificial Neural Network with Backpropagation algorithm. The research data used comes from the Central Bureau of Statistics of North Sumatra from 2012 until 2017. This research will use five architectural models namely 4-5-1, 4-7-1, 4-9-1, 4-10-1 and 4-11-1. The best model of the five models is 4-7-1 with a 100% accuracy rate, with a time of 27 seconds. The error rate used is 0.001 - 0.05. Thus, this model is good enough to predict Export Value in North Sumatra, because its accuracy reaches 100%.